ANALISIS PELUANG DAN TANTANGAN INDONESIA DALAM MENINGKATKAN EKSPOR MAKANAN OLAHAN: STUDI KASUS NEGARA TUJUAN EKSPOR VIETNAM - . Ernawati (Buletin Ilmiah Litbang Perdagangan, 2010)
In 2007, the government of Indonesia had a target to increase export of processed food products by 6.6% of 2007’s export value; it is about US$ 148.67 million. Of this value 63.02% (US$93.77 million) was targeted coming from Vietnam’s export. How Indonesia should reach this target?. utilizing the data provided by the Ministry of Trade, International Trade Center (ITC), and World Integrated Trade Solution (WITS) the study has tried to answer this question. This study has the objectives: (1) to determine Indonesian opportunity to increase processed food products in Vietnam market by using trade performance indicator, and (2) to determine the comparative advantage of the processed-food products which already identified in the first step using the Revealed Comparative Index (RCA). This study also utilized the primary data collected from the interview.This study concluded that Indonesia still had opportunity to increase exports to Vietnam, particularly on processed food products on which Vietnam does not has competitive advantage. These products included HS 15 (Animal, vegetable fats and oils, cleavage products, etc), 08 (edible fruits, nuts, peel of citrus fruit, melons) , HS 03 (Fish, crustaceans, molluscs, aquatic invertebrates nes), HS 09 (Coffee, tea, maté and Spices), 24 HS (Tobacco and manufactured tobacco substitutes) and HS 21 (Miscellaneous edible preparations). However, this opportunity was even bigger if Indonesia can improve its competitiveness and products value added. It can be done by enhancing the products packaging.